THE END OF HISTORY, THE DESTRUCTION OF THE STORY AND THE DEATH OF THE HERO IN POSTMODERN DISCOURSE - Sedrakyan, Anush (Armenian Folia Anglistika, 2023)
The issue of the narrative is closely linked to the formation of the universal story and the individual interpretation of it within the dimensions of time, space and action. Postmodernism demonstrates the proclivity to destroy these three dimensions, in other words, to deconstruct them. The most effective way to destroy the story, and even worse, the universal story is to deprive it of the goal, and linear development, where past, present and future are carefully outlined, and the hero envisages the end of the story as the natural, logical and supernatural consequence of his actions or even inactions.
Keywords: postmodernism; destruction; death; misinterpretation; transformation; non-existence; intellectual demand; mythology; punishment; collective unconsciousness